2021
DOI: 10.1039/d1sc03007h
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient on-DNA amide couplings promoted by micelle forming surfactants for the synthesis of DNA encoded libraries

Abstract: Highly efficient forward and reverse on-DNA amide couplings were developed exploiting hydrophobic linkers in combination with the micelle forming surfactant TPGS-750M. The method is highly effective for a wide range of substrates in the synthesis of DNA-encoded libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Alternatively, as Cycle 1 inputs, a carboxyl linker can react with amino substrates such as esters of amino acids. However, due to its poorly known instability during specific chemical conversions, as observed in our and others' work, [26] this form of reverse amide linkage has been infrequently employed for DEL synthesis. The limitations of available linkers for DEL synthesis prompted us to create alternatives.…”
Section: Introductionmentioning
confidence: 80%
“…Alternatively, as Cycle 1 inputs, a carboxyl linker can react with amino substrates such as esters of amino acids. However, due to its poorly known instability during specific chemical conversions, as observed in our and others' work, [26] this form of reverse amide linkage has been infrequently employed for DEL synthesis. The limitations of available linkers for DEL synthesis prompted us to create alternatives.…”
Section: Introductionmentioning
confidence: 80%
“… a Reported reaction conversions from ref . b Reported reaction conversions from ref . c Reported reaction conversions from ref . …”
Section: Resultsmentioning
confidence: 99%
“…One solution to the challenge of performing reactions in aqueous media is to use micellar surfactants . We have reported the use of the surfactant TPGS-750-M to promote on-DNA Suzuki–Miyaura and amide coupling reactions . Both reactions proceed with the excellent conversion to the desired products with minimal side reactions.…”
Section: Introductionmentioning
confidence: 98%
“…[30] Waring et al investigated both C-to-N and N-to-C amidations under micellar conditions. [31] Initial investigations showed that the structure of the linker between the oligonucleotide and organic handles greatly affects the outcome. While the reaction with the commonly employed PEG-4 linker performed poorly, a more hydrophobic hexadecanoic acid linker provided promising results in the N-to-C coupling (Scheme 8).…”
Section: Amide Bond Formationmentioning
confidence: 99%
“…Waring et al. investigated both C ‐to‐ N and N ‐to‐ C amidations under micellar conditions [31] . Initial investigations showed that the structure of the linker between the oligonucleotide and organic handles greatly affects the outcome.…”
Section: Micellar Synthesis Of Dna‐tagged Moleculesmentioning
confidence: 99%